Heme oxygenase 2: endothelial and neuronal localization and role in endothelium-dependent relaxation. - Zakhary, R (1996)
Heme oxygenase 2 (HO-2), which synthesizes carbon monoxide (CO), has been localized by immunohistochemistry to endothelial cells and adventitial nerves of blood vessels. HO-2 is also localized to neurons in autonomic ganglia, including the petrosal, superior cervical, and nodose ganglia, as well as ganglia in the myenteric plexus of the intestine. Enzyme studies demonstrated that tin protoporphyrin-9 is a selective inhibitor of HO with approximately 10-fold selectivity for HO over endothelial nitric oxide synthase (NOS) and soluble guanylyl cyclase. Inhibition of HO activity by tin protoporphyrin 9 reverses the component of endothelial-derived relaxation of porcine distal pulmonary arteries not reversed by an inhibitor of NOS. Thus, CO, like NO, may have endothelial-derived relaxing activity. The similarity of NOS and HO-2 localizations and functions in blood vessels and the autonomic nervous system implies complementary and possibly coordinated physiologic roles for these two mediators.